The landscape of T and B lymphocytes interaction and synergistic effects of Th1 and Th2 type response in the involved tissue of IgG4-RD revealed by single cell transcriptome analysis. Issue 133 (December 2022) - Cai, Shaozhe; Chen, Yu; Hu, Ziwei; Zhou, Tianshu; Huang, Yanli; Lin, Shengyan; Gao, Rongfen; Zhong, Jixin; Dong, Lingli
Abstract: Objectives: To investigate the landscape of T-B cell interaction, immune receptor profiles and effects of different types of immune responses in the involved tissues of IgG4-RD. Methods: Single cell RNA sequencing, bulk sample RNA sequencing, immune receptor repertoire analysis (both BCR and TCR), multi-color flow cytometry, and in-vitro assays with model cells (e.g. EBV-immortalized B cells from IgG4-RD patient) and histologic methods were applied to investigate the immunopathological features of IgG4-RD from multiple aspects. Results: Ectopic germinal center formation was observed in IgG4-RD patients at advanced disease stage, and a large part of B cells in involved tissue were germinal center B cell-like. Germinal center reaction in IgG4-RD led to the irregularities of both TCR and BCR clones in the involved tissues, and limited clonal overlaps among different samples. Enhanced Th1- and Th2-type responses were observed in involved tissues of IgG4-RD and patients with both increased Th1- and Th2-type response related cell subsets possessed more severe inflammatory indices. Analyses to the origin of IGHG4 transcripts in IgG4-RD indicated that IgG4 could be switched from IgM directly, or from other IgG subclasses. In vitro assays with EBV-immortalized B cells, fibroblasts and epithelial cells revealed the effects of Th1-type and Th2-type responses on germinal center reaction, ectopic expression of MHC-II molecules, and formation of tertiary lymphoid structures. Conclusions: Synergistic effects of Th1- and Th2-type responses were involved in the pathogenesis of IgG4-RD via their influences on both acute inflammatory processes and the chronicity and complexity of IgG4-RD. Graphical abstract: Potential synergistic effects of Th1- and Th2-type responses in the pathogenesis of IgG4-RD Image 1 Highlights: The landscape of T-B cell interaction in involved tissue of IgG4-RD was described via scRNA-Seq & immune repertoire analysis. Strong ectopic germinal center reaction and potential epitope spreading is observed in the involved tissues. IgG4 can be switched in both direct (from IgM) and sequential ways (from other IgG subclasses) in IgG4-RD. Synergistic effects of Th1- and Th2-type responses may synergistically promote the pathogenesis of IgG4-RD.